ANALISIS KUALITAS MANAJEMEN BIMBINGAN DAN SISTEM PENDUKUNG DI SD GENIT 33 MORU 1 - Marsia Alomau; Mita Lodia Sing, Daud Hugo Kafomay, Yessy Mata, Petrus Mau Tellu Dony, Yermia S Wabang (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Abstract This study aims to describe and address the management and support systems of guidance services at SD GMIT 33 Moru 1. Guidance services in elementary schools play an important role in helping students overcome learning, social, and emotional problems. However, the implementation often faces obstacles such as limited resources, lack of teacher training, and suboptimal coordination among related parties. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results showed that the guidance management at SD GMIT 33 Moru 1 is still simple and not yet systematically structured. Support systems such as the involvement of classroom teachers, school principals, and parents have begun to function but are not yet maximized. Improvement efforts are directed toward enhancing teacher competence in providing guidance services, strengthening coordination among school stakeholders, and developing well-planned guidance programs. With proper management and systemic support, school guidance services can operate more effectively and positively contribute to students' holistic development.